Leitliniengerechte Therapie des Morbus Crohn: Aktuelle Handlungsempfehlungen - Fischer, Sören; Neurath, Markus (Gastroenterologe, 2019)
Background: Crohn’s disease is a complex condition with rising incidence worldwide. The approval of multiple new therapeutic options results in growing challenges for physicians and guidelines. Objectives: The aim of this paper is to describe a plausible algorithm for the treatment of Crohn’s disease based on the current scientific knowledge. Materials and methods: We refer to the current guidelines of the German Gastroenterology Organization (DGVS), the European Crohn’s and Colitis Organization (ECCO), the American College of Gastroenterology (ACG) as well as the drug professional information. Results: The therapy of Crohn’s disease depends on the affected tract regions, severity of inflammation, individual patient characteristics, previous therapies, and the patient’s preferences. Conclusions: The therapeutic options in Crohn’s disease are constantly evolving. The prediction of therapy response is a continued challenge for medical science. In the principle of participatory medicine, shared decision-making of patient and physician leads to better adherence to the therapy.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Biologicals; Colorectal surgery; Drug therapy; Glucocorticoids; Inflammatory bowel diseases